0482 Exposure to hexavalent chromium and nickel and lung cancer risk: a pooled analysis of case-control studies from europe and canada. (21st August 2017) - Behrens, Thomas; Pesch, Beate; Vermeulen, Roel; Olsson, Ann; Schüz, Joachin; Portengen, Lützen; Kendzia, Benjamin; Kromhout, Hans; Straif, Kurt; Brüning, Thomas; ,
Abstract : Background: There is limited evidence regarding the exposure-effect relationship of exposure to hexavalent chromium (CrVI) and nickel (Ni) with lung cancer. We estimated the cumulative exposure for CrVI and Ni and assessed exposure-effect relationships for lung cancer risk by sex, smoking status, and histological subtypes. Methods: Fourteen case-control studies (1985–2010) from Europe and Canada were pooled, including 16 901 lung cancer cases (80% men) and 20 965 controls (78% men). Cumulative exposure to CrVI and Ni were estimated. Unconditional logistic regression models were fitted to estimate odds ratios (OR), 95% confidence intervals (CI), and exposure-effect trends adjusted for smoking and occupations with recognised lung cancer risk. Results: The OR for the highest quartile (>98.95 μg/m 3 -years) of cumulative CrVI-exposure was 1.33 (95% CI 1.20–1.48) in men and 1.04 (95% CI 0.48–2.23) in women. In never smokers, the OR for ever CrVI-exposure was 1.37 (95% CI 1.09–1.73) in men, and OR=1.09; 95% CI 0.70–1.69 in women. The OR for the highest quartile of cumulative Ni-exposure (>77.53 μg/m 3 -years) was 1.30 (95% CI 1.16–1.45) in men and 1.29 (95% CI 0.59–2.81) in women. The OR for ever Ni-exposure was 1.22 in never smokers for both sexes. Conclusions: Our results showed an exposure-dependent excess risk of lung cancer by occupational exposure to Ni in both sexes, and for CrVI in men. The pattern for CrVI in women was less clear. Analysis of an interaction between Cr- and Ni-exposure was impaired by a high correlation of these agents in metal fumes.